Definition and quality requirements for stereotactic radiotherapy: consensus statement from the DEGRO/DGMP Working Group Stereotactic Radiotherapy and Radiosurgery - Guckenberger, Matthias; Baus, Wolfgang W.; Blanck, Oliver; Combs, Stephanie E.; Debus, Juergen; Engenhart-Cabillic, Rita; Gauer, Tobias; Grosu, Anca-Ligia; Schmitt, Daniela; Tanadini-Lang, Stephanie; Moustakis, Christos (Strahlentherapie und Onkologie, 2020)
Stereotactic radiotherapy with its forms of intracranial stereotactic radiosurgery (SRS), intracranial fractionated stereotactic radiotherapy (FSRT) and stereotactic body radiotherapy (SBRT) is today a guideline-recommended treatment for malignant or benign tumors as well as neurological or vascular functional disorders. The working groups for radiosurgery and stereotactic radiotherapy of the German Society for Radiation Oncology (DEGRO) and for physics and technology in stereotactic radiotherapy of the German Society for Medical Physics (DGMP) have established a consensus statement about the definition and minimal quality requirements for stereotactic radiotherapy to achieve best clinical outcome and treatment quality in the implementation into routine clinical practice.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Definition; Radiosurgery; SBRT; SRS; Stereotactic Body Radiotherapy